A Case Series of BCOR Sarcomas With a New Splice Variant of BCOR/CCNB3 Fusion Gene - KYRIAZOGLOU, ANASTASIOS (In Vivo, 2020)
Background/Aim: Undifferentiated round cell sarcomas are a heterogeneous group of sarcomas. Identification of BCOR alterations, such as BCOR/CCNB3 and BCOR/MAML3 fusion genes and BCOR ITD has recently contributed in the precise diagnosis of these neoplasms, defining a new entity of the current classification of soft tissue and bone sarcomas. BCOR sarcomas share both morphological and genetic characteristics distinct from Ewing sarcomas. The scope of our study was to retrospectively identify BCOR sarcomas and find the correlations with the clinical outcome of these patients. Patients and Methods: Histopathology and immunohistochemistry of pediatric tumor samples were combined with molecular testing (PCR) and fluorescent in situ hybridization to find BCOR sarcomas. Results: We, herein, present our experience with BCOR sarcomas in a referral center of Greece. Moreover, we report in one case the detection of a variant BCOR/CCNB3 fusion not previously described. Conclusion: We are the first to report a splice variant of BCOR/CCNB3 which reveals the central position of BCOR in the oncogenesis of these tumors, furthermore we highlight the importance of molecular diagnostics in Ewing-like sarcomas and discuss the current treatment options for this rare entity.